ANALISIS MENDALAM PENINGKATAN KETERAMPILAN ARGUMENTASI ILMIAH SISWA PADA PEMBELAJARAN FISIKA - Zakaria, Ahmad; Irvani, Asep Irvan; Muhajir, Siti Nurdianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the improvement of physics learning in improving students' argumentation skills. The method used in this study is the Systematic Literature Review (SLR) with the PRISMA analysis model. The process includes several steps, namely formulating research questions, conducting searches sourced from the Semantic Scholar Database, using three keywords, namely High school; scientific argumentation; Physics Learning in 2014 to 2024. Furthermore, the next stage is to conduct an initial filtering based on the year of publication, followed by a second filtering based on the research criteria to be analyzed. After that, an analysis of the literature published in 2014 to 2024 was carried out and the results were reported in this literature study. This study shows that students' scientific argumentation skills are crucial skills in physics learning that can be improved through learning models, because these models help students understand good argumentation structures and practice developing scientific arguments effectively.